Design of power over wi-fi rectifier circuit for IoT based sensor application through simulation - Aini Azman, Aiman Saifullah; Ramli, Nor Azuana (Penerbit Universiti Malaysia Pahang, 2020)
Energy harvesting has been a phenomena throughout the year as it produces renewable clean energy which not only benefit to the user but also to the environment. Radio frequency energy is among the possible choice that can be harvested for low power usage application. By doing so, low power application such as IoT based sensors can eliminate usage of input power from battery which has limited supply over time or restrained from limited cable length. The objectives of this study are to design a power over Wi-Fi rectifier circuit for IoT based sensor application, analyze the effect of different type of diodes to the power over Wi-Fi rectifier circuit, and determine of minimum voltage required to power an IoT sensor. Cockcroft Walton voltage multiplier configuration was chosen as the rectifier circuit to be employed in the simulation by using Multisim software. With two different Schottky diodes, the output were recorded, and analyzed. Both diode has achieved the minimum required voltage of 3.3V and above for IoT sensors at stage 3. Among the diodes, BAT68 has recorded better output with 4.145V compare to diode BAT17 with 4.090V. Output of diode BAT68 also has reach its stable condition fast than diode BAT17. This configuration can be used and applied in prototype for future study. Even though there are many other factors that need to be considered, radio frequency energy harvesting should be explored more as it promotes clean energy and longevity lifespan as the world are moving wireless in many tasks.